Proteomic Analysis of Hydro primed Seeds of Maize Hybrid and its Parental Lines - HEENA RASOOL MIR; SHIV K YADAV; ZAKIR HUSSAIN; PRIYA RANJAN KUMAR; SANGITA YADAV (Seed Research, 2026)
Maize (Zea mays L.) known as queen of cereals and globally it is among the most widely grown field crops. Hydropriming is an efficient method to improve seed performance under unfavourable arid and semi-arid maize producing regions. Though the hydropriming process is simple and offers huge potential to increase uniform plant stand, yet the molecular mechanism behind it is still unknown. Studies on the changes in expression of proteins due to hydropriming in maize seeds were attempted. In this study, genetically pure seeds of maize hybrid; PEHM 5 and its parents (Female – CM 150, Male - CM 151) were taken and divided in two groups before imbibing them in water for 30 h at 25°C. In first group, hydroprimed seeds were dried to their original moisture content under shade at room temperature at 25 ±2°C while in second group the hydroprimed seeds were dried using the blotting paper and immediately evaluated for germination and differential proteomic analysis with untreated seeds. Increased abundance of proteins belonging to the family of antioxidant enzymes in soaked and primed maize seeds might have resulted in significantly improved seed germination. This also revealed that different proteins are expressed during imbibition and different phases of seed priming. The differential expression of protein spots between the primed and control seeds could possibly be the protein markers for enhanced seed vigour.